The impact of heart irradiation dose on cardiac injury and survival in lung cancer patients after radiotherapy - Li, Bingchen (Frontiers in Oncology, 2025)
Thoracic radiotherapy is a primary treatment modality for lung cancer, with approximately two-thirds of patients receiving it. The association between heart dose and post-radiotherapy survival and cardiac injury represents a critical area of contemporary radiotherapy research, yet understanding of radiation-induced heart disease (RIHD) in lung cancer remains incomplete. This review synthesizes literature on the effects of heart dose on survival and substructure-specific cardiac injury in lung cancer patients, evaluating thresholds for reversible and irreversible damage to cardiac substructures. We further summarize key mechanisms underlying RIHD.